2002
DOI: 10.1152/jn.00773.2000
|View full text |Cite
|
Sign up to set email alerts
|

Motor Facilitation While Observing Hand Actions: Specificity of the Effect and Role of Observer's Orientation

Abstract: Maeda, Fumiko, Galit Kleiner-Fisman, and Alvaro Pascual-Leone. Motor facilitation while observing hand actions: specificity of the effect and role of observer's orientation. J Neurophysiol 87: 1329 -1335, 2002; 10.1152/jn.00773.2000. Action observation enhances cortico-spinal excitability. Here we tested the specificity of this effect and the role played by the orientation of the observer. Ten normal subjects observed video clips of right hand performing three different finger movements (thumb ab-/adduction, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
219
7
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 367 publications
(268 citation statements)
references
References 44 publications
33
219
7
3
Order By: Relevance
“…In addition, our results support a neurophysiological advantage for self-related stimuli (Jackson, Meltzoff, & Decety, 2006;Maeda, Kleiner-Fisman, & Pascual-Leone, 2002) as subsequent to IPL-stimulation, -suppression only decreased for the egocentric hands movements. Given that we observed no effect on -suppression during observation of allocentric hands movements subsequent to stimulation, we suggest that other neural mechanisms are involved in the processing of allocentric hands movements.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, our results support a neurophysiological advantage for self-related stimuli (Jackson, Meltzoff, & Decety, 2006;Maeda, Kleiner-Fisman, & Pascual-Leone, 2002) as subsequent to IPL-stimulation, -suppression only decreased for the egocentric hands movements. Given that we observed no effect on -suppression during observation of allocentric hands movements subsequent to stimulation, we suggest that other neural mechanisms are involved in the processing of allocentric hands movements.…”
Section: Discussionsupporting
confidence: 80%
“…Typically, correlational studies investigating perspectives as an indication of self-other differentiation have shown that egocentric stimuli induce greater neurophysiological and behavioural responses compared to allocentric stimuli. For example, it has been observed: greater cortical activity in the sensorymotor cortex (Jackson et al, 2006), greater visuomotor interference (Bortoletto et al, 2013;Vogt et al, 2003) and larger motor-evoked potentials (MEPs) as induced by transcranial magnetic stimulation (TMS) during the observation of egocentric movements (Maeda et al, 2002). However, these correlational reports have not always been consistent; Alaerts and colleagues (2009) reported that MEPs are not necessarily larger for egocentric movements per se; rather, MEP's are larger for an egocentric right hand and for an allocentric left hand.…”
Section: Introductionmentioning
confidence: 99%
“…both these assumptions are hard to reconcile with what is known about the organization of the cerebral cortex. Most importantly, TMS studies have shown a clear congruence between the observed motor act and the activated motor representation [32][33][34][35][36] . Thus, if higher-order sensory information describing a motor act reaches motor neurons that encode that same motor act, these motor neurons are mirror neurons by definition.…”
Section: Movementmentioning
confidence: 99%
“…The initial evidence for this mechanism was based on TMS experiments which indicated that the observation of the movements of others results in an activation of the muscles involved in the execution of those movements [32][33][34][35][36] . Additional support comes from eeG and MeG studies showing that the observation of movements without a goal desynchronizes the rhythms recorded from motor areas [57][58][59][60][61][62][63][64] .…”
Section: Box 1 | Mirror Neurons In Other Parietal Areasmentioning
confidence: 99%
“…This internal PMC representation is probably used for their understanding Fadiga, Fogassi, Pavesi, & Rizzolatti, 1995;Grafton, Arbib, Fadiga, & Rizzolatti, 1996;Grè zes, Armony, Rowe, & Passingham, 2003;Grè zes, Costes, & Decety, 1999;Hari et al, 1998;Iacoboni et al, 1999;Kohler et al, 2002;Maeda, Kleiner-Fisman, & Pascual-Leone, 2002). This passive automatic activation of PMC-motor circuits, without the production of an actual movement, seems to be the counterpart of the compelling tendency to move of the PFC-lesioned patients.…”
Section: Introductionmentioning
confidence: 99%